ST ELEVATIONS DURING LEFT ATRIAL APPENDAGE OCCLUSION (LAAO) SECONDARY TO WATCHMAN DEVICE COMPRESSION OF THE LEFT CIRCUMFLEX (LCX) ARTERY: A CASE REPORT - Lorelle Sun, MS (Elsevier, 2024)
Therapeutic Area: Ischemic Stroke Case Presentation: A 67-year-old male, with paroxysmal atrial fibrillation (AF), CHADS-VASc 3, and HAS-BLED 3, was admitted for elective WATCHMAN left atrial appendage occlusion (LAAO). Following transesophageal echocardiography (TEE) measurements of the left atrial appendage (LAA), the 24-mm WATCHMAN FLX was selected given manufacturer recommendation of 10-27% compression rate. During the procedure, initial device deployment was successful with appropriate position, compression, and closure in setting of a prominent pectinate ridge. However, within minutes, blood pressure dropped, and electrocardiogram (ECG) showed nonsustained ventricular tachycardia and inferolateral ST elevations. Device compression was 18-23% and shoulder was 0-20%; there was no flow around the device. In the 90° TEE view, device edge to left circumflex (LCx) artery measured 2.4 mm. Upon device recapture, hemodynamic and ECG abnormalities resolved quickly. There was no evidence of air embolism or left atrial thrombus. Given mechanical compression of LCx by a properly sized and positioned device, a decision was made to discontinue the procedure. Postoperative ECG and imaging showed no acute changes. Patient remained asymptomatic and hemodynamically stable upon discharge. Background: Reducing stroke risk is paramount in patients with AF, though chronic anticoagulation confers a major bleeding risk. Research has consistently highlighted the comparable efficacy of percutaneous LAAOs to oral anticoagulation in preventing stroke among nonvalvular AF patients. WATCHMAN LAAOs have increased in prevalence since its approval by the Food and Drug Administration in 2015. Despite their relative safety, a rare yet critical complication involves compression of the LCx coronary artery. Conclusions: This represents the second reported case of LCx coronary artery compression by a WATCHMAN, resulting in hemodynamic instability and acute ST elevations that resolved with device removal. This complication warrants vigilance as recognition should lead to device withdrawal. Further investigation into patient specific risk factors is warranted to stratify risk prior to device implantation. Individual differences, such as preexisting coronary artery disease and proximity of left coronary artery and its branches to LAA should be considered. While current guidelines recommend sizing devices up for over-compression to minimize peri-device leaks, our case highlights that even within recommended compression ratios, mechanical coronary artery compression remains a risk.